PADDY'S PERFORMANCE IN MALAYSIA - Noorfazreen Mohd Aris; Mohd Faizal P.Rameli; Norizah Mohamed @ Haji Daud; Sharipah Amirah Haji Abas; Norajila Che Man (Journal of Islamic, Social, Economics and Development, 2018)
Paddy is an important food commodity in Malaysia. In order to materializegovernment’s attention on this matter, some policies have been constructed. Starting off withFirst National Agricultural Policy (NAP1) in 1984, it is then followed by Second NationalAgricultural Policy (NAP2) in 1992, Third National Agricultural Policy (NAP3) in 1998 andNational Food Security Policy (NFSP) in 2008 as well as National Agrofood Policy (NAP)which has been implemented from 2011 until present. Insufficiency of this main food sourcewill result in food deprivation throughout the country, leading to the need of importation. Inrelation to that, this research focused on the statistic of paddy production within the policies’implementation period from 1984 until 2015. This qualitative research uses library researchVolume: 3 Issue: 11 [June, 2018] pp. 51-61]Journal of Islamic, Social, Economics and DevelopmenteISSN: 0128-1755Journal website: www.jised.comm52approach to collect data which involves a lot of materials including the 5th-11th MalaysiaPlan, DPN1 until DPN3 and economy reports. Data collected were analysed via contentanalysis method. From the data, research finds that the development of paddy agriculturalsector is on rise but still inadequate to support nation’s need and its dependability onimportation.